Cardiovascular responses to sugary drinks in humans: galactose presents milder cardiac effects than glucose or fructose. - Charrière, Nathalie; Loonam, Cathriona; Montani, Jean-Pierre; Dulloo, Abdul; Grasser, Erik (European Journal of Nutrition, 2017)
Purpose: There is increasing interest into the potentially beneficial effects of galactose for obesity and type 2 diabetes management as it is a low-glycemic sugar reported to increase satiety and fat mobilization. However, fructose is also a low-glycemic sugar but with greater blood pressure elevation effects than after glucose ingestion. Therefore, we investigated here the extent to which the ingestion of galactose, compared to glucose and fructose, impacts upon haemodynamics and blood pressure. Methods: In a randomized cross-over study design, 9 overnight-fasted young men attended 3 separate morning sessions during which continuous cardiovascular monitoring was performed at rest for at least 30 min before and 120 min after ingestion of 500 mL of water containing 60 g of either glucose, fructose or galactose. These measurements included beat-to-beat systolic and diastolic blood pressure, heart rate deduced by electrocardiography, and stroke volume derived by impedance cardiography; these measurements were used to calculate cardiac output and total peripheral resistance. Results: Ingestion of galactose, like glucose, led to significantly lesser increases in systolic, diastolic and mean blood pressure than fructose ingestion ( p < 0.05). Furthermore, the increase in cardiac output and reduction in total peripheral resistance observed after ingestion of glucose were markedly lower after galactose ingestion ( p < 0.01). Conclusions: Galactose thus presents the interesting characteristics of a low-glycemic sugar with mild cardiovascular effects. Further studies are warranted to confirm the clinical relevance of the milder cardiovascular effects of galactose than other sugars for insulin resistant obese and/or diabetic patients with cardiac insufficiency.